THE VECTOR OF PRAYER MOVEMENT TO HEALTH - Suherman Suherman; Nurhidayat Nurhidayat; Masyitoh Chusnan; Tria Astika; Dadang Herdiansyah; Nazarwin Saputra; Alidina Nur Afifah (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
The prayer movement is an alternative exercise in endurance that is appropriate for Muslims to face the development of a world that is demanded with speed and endurance demanded with excellent muscle speed and endurance. Psychotherapy as a health worker has an important role in the effort to provide health services per its field, namely developing, maintaining, and restoring movement and body functions in life which includes impairments, functional limitation, and disabilities, which have a comprehensive, integrated, and sustainable nature involving roles. Some of the prayer movements that can be analyzed in the vector are the takbiratul ihram movement, the ruku’ movement, the i'tidal movement, and the prostration movement. Prayer is any word or deed that will form the essence of praying to Allah. If one of these pillars does not exist, then prayer is not considered syar'i nor can it be replaced by prostration. Prayers are not only the main practice in the hereafter but the most proportional prayer movements for the anatomy of the human body. Even from a medical point of view, prayer is a storehouse of medicine for various types of diseases. Allah, the Creator, knows exactly what His creation, especially humans really need.